Advertising and a New Social Control - Boeira, Marino (2008)
Although Brazil is often classified as a third and fourth world country, it is beyond doubt that there are pockets of consumption typical of the first world. Even if these pockets correspond to 20% or 30% of total Brazilian population, they mean 30 or 40 million consumers living in the South and Southeast, and also in the capitals and large cities of virtually all Brazilian states. These people are bombarded daily by an advertising barrage that is not due in quality and quantity to consumers in Europe, the United States or Japan. The question to be discussed is how all this mass of advertisements, video-tapes, movies, jingles, spots and direct mailings is received by society and to what extent it is amenable to critical receptivity.